How can the concept of public value influence U.K. utility regulation?. (October 2021) - Cave, Martin; Wright, Janet
Abstract: There is much recent debate about extending the purposes of investor-owned firms to embrace the broader interests of a variety of stakeholders. Regulatory decisions in network industries already involve extensive use of centralised social cost-benefit analysis to capture some aspects of public value. A gap remains that might be filled by a decentralised process in which the regulator supports firms in expanding their purposes to include the pursuit of public value, identified by regulated firms in collaboration with consumers and citizens, and delivered in innovative and entrepreneurial ways. Based on a preliminary case study, we conclude that the approach has a role, but its success depends critically upon the companies fully embracing the revised purposes. Highlights: How can regulators encourage investor-owned utilities to seek objectives beyond profit, including public value? Using a case study, we discuss how a regulator can engage regulatees to seek out and provide such benefits. We conclude that it can be done, provided that the regulated form is willing to extend and change its purposes.